Characterization of Tumor-immune Microenvironment by High-throughput Image Analysis of CD8 Immunohistochemistry Combined With Modified Masson's Trichrome. (September 2021) - Havnar, Charles; Lau, Shari; Hung, Jeffrey; Eastham-Anderson, Jeff; Espiritu, Carmina; Rangell, Linda; Koeppen, Hartmut; Ziai, James; Foreman, Oded
With the advent of checkpoint inhibitors, there is increasing need to study the dynamics of CD8+ T-cells in the tumor microenviroment. In this article, we describe a semi-automated method to quantify and interrogate spatial relationships between T-cells and collagenous stroma in human and mouse tissue samples. The assay combines CD8 immunohistochemistry with modified Masson's trichrome. Slides are scanned and digital images are analyzed using an adjustable MATLAB algorithm, allowing for high-throughput quantification of cytotoxic T-cells and collagen. This method provides a flexible tool for unbiased quantification of T-cells and their interactions with tumor cells and tumor microenvironment in tissue samples.